Sistem Navigasi Waypoint Pada Robot Beroda Berdasarkan Global Positioning System Dan Filter Kalman - A. Ashar Ashari; Eko Setiawan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wheeled robot is one of the most popular categories of mobile robots in the field of its science development. By its functional aspect, a wheeled robot is expected to be able to assist humans in terms of optimized transportation, unmanned exploration vehicle, and etc. The wheeled robot development will continue to run, and as well as its problem of sensor readings, positioning, and navigation system. Waypoint takes an important part in terms of developing navigation systems. In its application, waypoint navigation systems on a wheeled robot are used for reading a correcting position mistake, from GPS data alongside a sensor capable to pinpoint a heading and acts like a compass that can be able to establish a rotational motion. This research has the aim to improve the accuracy of reading data from the GPS module with or without implementing the Kalman Filter and also establishing rotational motions. The results of the research conducted, it was concluded that the accuracy of the magnetometer sensor is at the limit around 1Â° - 2 Â° at the fault tolerance limit with testing parameters 6.1, 7.1, 8.1, 9.1, and 10.1. From the results of the GPS module, it was found that the level of module accuracy varies but is still within a 10m success radius